Judaism in late antiquity. - Neusner, Jacob, 1932-; Avery-Peck, Alan J. 1953-; Chilton, Bruce. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2000)
Thirteen foremost scholars describe the views of death, life after death, resurrection, and the world-to-come set forth in the literary evidence for late antique Judaism. The volume covers the vie w of Scripture as a whole as against other Israelite writings; distinct parts of Scripture such as Psalms and the Wisdom literature; apocalyptic and the non-apocalyptic pseudepigraphic literature, Philo; Josephus; the Dead Sea Scrolls; earliest Christianity (the Gospels in particular); the Rabbinic sources; the Palestinian Targums to the Pentateuch; and, out of material culture, the inscriptional evidence. The result is both to highlight the range of available perspectives on this important issue and to illuminate a central problem in the study of Judaism in late antiquity, phrased neatly as "One Judaism or many?" Here we place on display indicative components of Judaism in their full diversity, leaving it for readers to determine whether the notion of a single, coherent religion falls under the weight of a mass of documentary contradictions or whether an inner harmony shines forth from a repertoire of largely shared and only superficially-diverse data.